Seasonal energetic physiology in the ark shell Anadara kagoshimensis in response to rising temperature - Kang, Hee Yoon; Seong, Jaeeun; Kim, Changseong; Lee, Byeong Gweon; Lee, In Tae; Kang, Chang-Keun (Frontiers in Marine Science, 2022)
Knowledge of physiological responses of important shellfish species to rising temperatures is crucial in assessing the The physiological components of energy balance that support growth performance were measured seasonally at different exposure temperatures in the ark clams (Scapharca subcrenata) cultured in the shallow muddy bottom sediment in Yeoja Bay, Korea. We tested the effects of winter minimum (3–8 °C) and summer maximum (23–28 °C) temperature elevations on individual physiological processes (ingestion, respiration, egestion, and excretion) and the combined energetic physiology (scope for growth [SFG] and net growth efficiency [K2] measures). The seasonal cycle of dry flesh tissue weight (DW) was also investigated from January 2016 to November 2018, to compare its variation at contrasting cold vs. warm regimes. The rates of physiological components were related to DW, generating significant allometric equations. The weight exponents of the equations for ingestion rate and respiration rate were low at the winter minimum compared with the remaining season temperatures, indicating a higher thermal sensitivity in larger individuals. The physiological rates that were re-calculated for individual components based on estimates of the slope and intercept of the equations increased with increasing temperature, revealing an incapability of thermal acclimation and a temperature effect at seasonally different endogenous conditions. The thermal sensitivity (Q10) of the ingestion rate and respiration rate was reversed between the winter minimum and the summer maximum temperature elevations, yielding negative SFG and K2 values at 3 and 28 °C. Furthermore, the interannual difference in the seasonal cycle of clam DW displayed variations in the period of increment prior to spawning and the post-spawning loss/recovery in association with its energy balance status in the winter and summer temperature conditions. Overall, these results indicate that warming is projected to affect physiological performance and the seasonal DW cycle of clams in different manners between winter and summer: physiological benefits and advanced weight gain vs. heat stress and progressive weight loss, respectively. The mechanistic adjustment of the clam energy balance across thermal conditions seems to explain the recent advancement in its seasonal biological cycle, as well as the failure in spat collection and the mass summer mortality.